Capacity utilisation and performance at railway stations. Issue 3 (December 2017) - Armstrong, John; Preston, John
Abstract: As railway traffic levels increase in Britain and elsewhere, improved understanding of the trade-offs between capacity provision/utilisation and service quality is increasingly important, as Infrastructure Managers and Railway Undertakings seek to maximise capacity provision while maintaining service reliability and punctuality. This is particularly true of the stations and junctions forming the nodes and capacity bottlenecks of railway networks, for which the relationships between capacity utilisation and performance are less well understood than for their intermediate links. Following work undertaken for the OCCASION project on the calculation of nodal Capacity Utilisation Indices, and on the application of these techniques to the recalibration of the Capacity Charge element of the Track Access Charges in Britain, one objective of the DITTO Rail Systems project is the further investigation of the relationship(s) between capacity utilisation and performance, as indicated by congestion-related reactionary delay levels at railway stations and junctions. Historic timetable and delay data for selected stations have been used to investigate these relationships, which take the expected form and tend to suggest lower maximum capacity utilisation levels for stations than for the links between them. Work is ongoing to develop these datasets and relationships further, and to identify suitable capacity utilisation upper limits. Highlights: Capacity utilisation and performance (delay) data at several railway stations are assembled. Exponential relationships between capacity utilisation and delay are identified. The relationships identified vary, but demonstrate some general consistency. The indicative upper limits for capacity utilisation appear to be lower than for links.